Actuation-Induced stable crack growth in near-equiatomic nickel-titanium shape memory alloys: Experimental and numerical analysis. (15th June 2021) - Jape, S.; Young, B.; Haghgouyan, B.; Hayrettin, C.; Baxevanis, T.; Lagoudas, D.C.; Karaman, I.
Abstract: Shape Memory Alloy (SMA) actuation technology requires a thorough understanding of the failure response of these alloys under loading that involves thermal variations, termed "actuation" loading. In this paper, the experimental observation of stable crack growth in SMA compact tension specimens during temperature changes under constant bias loads is reported for the first time. The intrinsic damage mechanisms that promote crack advance are those reported in literature for nominally isothermal overload fracture, i.e., cleavage assisted by ductile void growth. Moreover, a numerical analysis is employed, and the resulting simulations are compared with the experimental data with the purpose of building confidence in the insight provided on the role of extrinsic mechanisms that further promote or impede crack advance. It is concluded that phase transformation plays a dual role on the crack growth kinetics by promoting crack growth when occurring in a fan in front of the crack tip and providing the toughness enhancement that results in stable crack growth when left in the wake of the advancing crack. While the latter is well known as transformation-induced toughness enhancement, the former has just been recently observed experimentally and is characteristic of SMAs subjected to actuation loading conditions.